Descriptive Study of Acute Appendicitis in Khost Specialized Hospital - Sherkhil, Naqibshah; Lakanwal, Qaiswer Shah; Zaki, Rahmatrahim; Gulsharif, Sherzad (Journal for Research in Applied Sciences and Biotechnology, 2023)
Background: Acute appendicitis is one of the most common acute surgical conditions in the United States. In 1886, Dr. Reginald Fitz first used the term acute appendicitis to describe an inflammatory condition of the right lower quadrant that was starting to be treated surgically with success (1). In the nineteenth century, Dr. Charles McBurney went on to author a series of papers describing appendicitis definitively as a surgical disease. According to his observation, this condition was commonly associated with focal pain and tenderness at one specific location in the right lower quadrant later became widely known as “McBurney’s point” (2, 3). Methods: This study was conducted in the surgical word of the post graduated hospital Khost in (1400-1401) hejri Shamsi year on 423 patients who were diagnosed and treated with acute appendicitis. The purpose of this study is to compare the incidence of disease with other studies which have been done in others countries in the terms of gender, age, and complications. Conclusions: The result of this research shows that acute appendicitis is more in men than women. Out of this group, 282 (66.66%) patients are men, and the remaining 143 (80.33%) are women. 316 (77.74%) Patients who has Appendicitis are form Khost province and the remaining 107 (25.29%) patients are form neighboring provinces. The ratio between men and women is 1.97:1.